Information needs and development of a question prompt sheet for upper extremity vascularized composite allotransplantation: A mixed methods study - Gacki-Smith, Jessica; Kuramitsu, Brianna R.; Downey, Max; Vanterpool, Karen B.; Nordstrom, Michelle J.; Luken, Michelle; Riggleman, Tiffany; Altema, Withney; Fichter, Shannon; Cooney, Carisa M.; Dumanian, Greg A.; Jensen, Sally E.; et al. (Frontiers in Psychology, 2022)
Background: People with upper extremity (UE) amputations report receiving insufficient information about treatment options. Furthermore, patients commonly report not knowing what questions to ask providers. A question prompt sheet (QPS), or list of questions, can support patient-centered care by empowering patients to ask questions important to them, promoting patient-provider communication, and increasing patient knowledge. This study assessed information needs among people with UE amputations about UE vascularized composite allotransplantation (VCA) and developed a UE VCA-QPS. Methods: This multi-site, cross-sectional, mixed-methods study involved in-depth and semi-structured interviews with people with UE amputations to assess information needs and develop a UE VCA-QPS. Qualitative data were analyzed by thematic analysis; quantitative data were analyzed by descriptive statistics. The initial UE VCA-QPS included 130 items across 18 topics. Results: Eighty-nine people with UE amputations participated. Most were male (73%), had a mean age of 46 years, and had a unilateral (84%) and below-elbow amputation (56%). Participants desired information about UE VCA eligibility, evaluation process, surgery, risks, rehabilitation, and functional outcomes. After refinement, the final UE VCA-QPS included 35 items, across 9 topics. All items were written at a ≤ 6th grade reading level. Most semi-structured interview participants (86%) reported being ‘completely' or ‘very’ likely to use a UE VCA-QPS. Conclusions: People with UE amputations have extensive information needs about UE VCA. The UE VCA-QPS aims to address patients’ information needs and foster patient-centered care. Future research should assess whether the UE VCA-QPS facilitates patient-provider discussion and informed decision-making for UE VCA.